Identity and Inequality among the Wawaga Valley Barai, Oro Province, PNG - Barker, T.R. (Anthropologica, 2022)
The question of leadership among the Barai, a Papuan mountain people, is considered. Although Barai ceremonial exchange is not incremental and thus not capable of providing a single gradient on which to rank the "bigness" of men, degrees of male power as expressed through identification with a hierarchy of totems serve to distinguish group leaders. The conflicts between the elder and younger brothers, and between contenders for leadership within one group are discussed in relation to inheritance, sorcery and the control of resources. It is concluded that hierarchy and competition have a different locus among the Barai than among peoples where incremental and enchained exchanges exist.